Knowledge, attitude and practicality of solat among the hospitalised patients - Azhari, Azni Shafinas; Mohamed, Rozilah @ Abdul Hadi; Che Ahmad, Aminudin; Abdullah, Nor Zamzila; Awang, Mohd Shukrimi; Ismail, Raffael (IIUM Press, 2022)
Introduction: A Muslim is obliged to perform solat five times every day at dedicated times. This must be performed regardless of the situation, either in ease or difficulty. The aims of this study were to investigate the awareness, knowledge and practicality of solat for sick Muslim patients when they hospitalised. Methods: A cross sectional study involving 160 patients was conducted between 18th July 2013 and 28th August 2016. A valid, self-administered questionnaire was given to all Muslim patients to assess the awareness, knowledge, and practicality of solat during illness. The questionnaires were distributed to hospitalised Muslim patients from six selected hospitals in Malaysia. Results: All 160 respondents are Muslim and know that solat is obligatory to be perform (100%). The majority of them 129 (80.6%) practice solat five times daily, while 26 (16%) practice it sometimes and five (3.1%) of them never perform it. However, only 103 (64.4%) were still practising solat when they were hospitalised, while 57 (35.6%) did not. More than half (56.9%) said that the pain and illness had limited their daily ritual practice. Overall, 113 (70.6%) of the respondents felt guilty when they unintentionally did not perform solat. Seventy (43.8%) patients said that the facilities in the hospital did not meet their expectations in terms of helping them to perform solat. Conclusion: This study implies that there is a need for measures and interventions to help Muslim people perform solat while hospitalised. We hope that by conducting proper training and upgrading the facilities, the level of awareness and practice can be improved.